2015
DOI: 10.1007/s13246-015-0337-6
|View full text |Cite
|
Sign up to set email alerts
|

BagMOOV: A novel ensemble for heart disease prediction bootstrap aggregation with multi-objective optimized voting

Abstract: Conventional clinical decision support systems are based on individual classifiers or simple combination of these classifiers which tend to show moderate performance. This research paper presents a novel classifier ensemble framework based on enhanced bagging approach with multi-objective weighted voting scheme for prediction and analysis of heart disease. The proposed model overcomes the limitations of conventional performance by utilizing an ensemble of five heterogeneous classifiers: Naïve Bayes, linear reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 20 publications
0
36
0
Order By: Relevance
“…The ranges of improvement shown by MLP in the objective specificity are −9.68 to 86.33 and −18.93 to 36.33 without and with resampling, respectively. From the experimental results, it is concluded that FMLP shows outperformance than recently developed ensemble classifiers ([14, 15]). As a part of the continuation of this research, we intend to process a very higher dimensional dataset with the major phases of feature selection and parameter evolution of the classifier.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The ranges of improvement shown by MLP in the objective specificity are −9.68 to 86.33 and −18.93 to 36.33 without and with resampling, respectively. From the experimental results, it is concluded that FMLP shows outperformance than recently developed ensemble classifiers ([14, 15]). As a part of the continuation of this research, we intend to process a very higher dimensional dataset with the major phases of feature selection and parameter evolution of the classifier.…”
Section: Discussionmentioning
confidence: 93%
“…References [14] through [16] are recent literature, and they have been referred to in our work as the base papers for every dataset (as has been earmarked in legends in Figure 2). The results of datasets corresponding to diseases like breast cancer, hepatitis, BUPA liver, Pima, Cleveland, and Parkinson have been compared with those of [14], whereas the results of Statlog, Spect, Spectf, and Eric have been compared with those of BagMOOV [15]. Thyroid disease results alone are compared with those of [16].…”
Section: Simulations and Resultsmentioning
confidence: 99%
“…Similarly, several techniques had been used [18] [19] to improve the accuracy of the classifiers for better prediction. Some of them are tabulated in Table 3.…”
Section: Literature Surveymentioning
confidence: 99%
“…A lot of effort has been put on to predict specific diseases [7], [8]. For instance, authors in [7] focus on predicting coronary heart diseases by mining text.…”
Section: Related Workmentioning
confidence: 99%